Dampak Konflik Sosial terhadap Ekspansi Lahan Perkebunan Sawit : Sebuah Kajian Literatur - Mohammad Bayu Irawan; Dewi K. Baderan; Fitryane Lihawa (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Social conflicts in the oil palm plantation sector have become an increasingly prominent issue in various regions, with impacts that not only affect the relationship between parties, but also threaten and affect the sustainability of the industry, aspects of people's lives and the environment. Conflicts are often rooted in land disputes, dissatisfaction with compensation, and the environmental impacts of unsustainable plantation practices. This study aims to explore the impact of social conflicts on oil palm land expansion. It is hoped that this research can provide clear information about the relationship between social conflicts and oil palm land expansion, so that it can be used to find better solutions in managing and developing oil palm land in a more sustainable and equitable manner. The methods used are literature studies and literature reviews. Literature study is a research design used in collecting data sources related to topics. The collection of data sources for literature studies is carried out with a database search tool that is used as a stage to search for literature sources. The screening results from the journals that are appropriate and needed are 9 national articles. Based on the activities and journals, it was found and analyzed that the impact of social conflicts on the expansion of oil palm plantation land can have environmental, economic, and social impacts.